Recurrent ischemic stroke in patients with atrial fibrillation: frequency, heterogeneity, prevention - L. A. Geraskina; M. M. Alieva; A. V. Fonyakin; M. Yu. Maximova; N. I. Garabova; M. G. Burzhunova (Атеротромбоз)
Introduction. For the prevention of recurrent ischemic stroke (IS) in patients with atrial fibrillation (AF), oral anticoagulants (OAC) are considered a priority. The comorbidity of AF patients raises a discussion about the non-alternative feasibility and exceptional clinical efficacy of OAC. The validity of the choice of a specific antithrombotic agent can be assessed using a dynamic assessment of the causes of the first and recurrent stroke in patients with AF.Aim. To assess the frequency recurrent IS and quality of medicament prevention therapy in patients with AF depend on heterogeneity of stroke leading pathogenetic mechanism.Materials and methods. The data from the register of 200 patients with IS and AF were analyzed. 55 (27.5%) patients suffered recurrent IS (24 (43,6%) men, 31 (56,4%) women, mean age 72,3 ± 10,2 years). The pathogenetic subtype of recurrent IS was determined, including a retrospective assessment of the pathogenetic subtype of a previous IS. We studied the presence and nature of antithrombotic therapy (ATT) preceding a second stroke.Results. The first IS was due to cardiogenic embolism in 36.4% of patients, the atherothrombotic subtype occurred in 18.2%, and the lacunar subtype in 34.5% of patients. Embolic stroke from an undetermined source (ESUS) - in 10.9% of patients. OACs were prescribed only to 31.7% of patients, antiplatelet agents - to 14.6% of patients, 53.7% of patients did not receive ATT. The leading pathogenetic subtype of recurrent stroke was cardiogenic embolism (70.7%), the frequency of lacunar stroke decreased (4.9%), and the frequency of atherothrombotic stroke remained unchanged. In 14 patients with recurrent stroke, AF was first detected, including all patients with ESUS.Conclusion. The proportion of recurrent stroke in patients with AF is 27.5%. Compared with the first stroke, recurrent stroke in patients with AF is characterized by an increase in the proportion of cardiogenic embolism up to 70.7%, which is due to the insufficient prescription of OAC, which must be recommended, including for patients with non-cardioembolic subtypes of stroke.